EXPLAINING EARNINGS MANAGEMENT THROUGH DIGITAL LITERACY, ESG, AND MANAGEMENT DEMOGRAPHICS - Musfi, Putri Nabila (Universitas Riau, 2026)
This study examines the determinants of accrual-based earnings management by analyzing the roles of executive digital literacy, ESG performance, management gender diversity, and management age. Earnings management is proxied by discretionary accruals estimated using the Modified Jones Model, which captures managerial discretion in accounting estimates rather than real operational manipulation. Using a quantitative design, the study analyzes firms included in the LQ45 index listed on the Indonesia Stock Exchange during 2022–2024. Through purposive sampling, 84 firm-year observations were obtained from companies consistently listed in the index, publishing complete financial statements, and not reporting consecutive losses. Financial institutions were excluded due to differences in reporting structures that limit the applicability of accrual-based models. Multiple linear regression analysis, preceded by descriptive statistics and classical assumption tests, was employed to test the hypotheses. The results indicate that executive digital literacy, management gender diversity, and management age positively influence accrual-based earnings management. In contrast, ESG performance negatively affects earnings management, suggesting that stronger sustainability performance constrains opportunistic reporting behavior